Penolakan Pasien Emergency oleh Rumah Sakit akibat Regulasi BPJS Kesehatan: Perspektif Hukum dan Etika - Wicaksono, Emirza Nur (LPPM Universitas Terbuka, 2025)
The refusal of patients in emergency conditions by hospitals that they do not meet the emergency criteria as stipulated by BPJS Kesehatan regulations raises critical legal and medical ethical issues. This study aims to analyze the juridical aspects and professional medical ethics related to such practices by examining the Indonesian Medical Code of Ethics as well as the legal provisions in Law Number 17 of 2023 on Health and Law Number 24 of 2011 on the Social Security Administering Body (BPJS Kesehatan). The research method used is a normative juridical approach through literature study. The findings indicate that, from a legal standpoint, hospitals and medical personnel are obligated to provide medical services to all patients in emergency situations without delay regardless their administrative status. Refusal to provide such services may be classified as a legal violation and may be subject to criminal, civil, and administrative sanctions. From the perspective of medical ethics, such actions are contrary to the principles of beneficence and non-maleficence and violate the Medical Code of Ethics. Therefore, BPJS administrative regulations must be aligned with legal and ethical principles in handling emergency cases to ensure the protection of patients’ rights and the continuity of equitable and professional health services. The study concludes that the refusal of emergency patients by hospitals due to unmet BPJS Health emergency criteria contradicts Indonesia’s positive law and the fundamental principles of medical ethics.